Avaliação do potencial de oxidoredução enantiosseletiva de bactérias termotolerantes do gênero Acetobacter. - Todaro, Adriana Reis (2005)
Membrane-bound NAD-independent alcohol dehydrogenase (NAD-independent ADH) from Acetobacter and Gluconobacter species has shown appreciable enantioselectivity on the oxidation of chiral primary and secondary alcohols. A NADIndependent alcohol dehydrogenase from mesophilic Acetobacter sp was isolated and characterized as a quinohaemprotein alcohol dehydrogenase QH-ADH. QHADH showed enantiopreference for the oxidation of (S)-enantiomer during the kinetic resolution of racemic secondary alcohols. Due to the growing interest for thermotolerant enzymes in the biocatalysis area, this study was performed to isolate acetic acid bacteria from vinegar factories in the northeast region of Brazil aiming to obtain a thermotolerant QH-ADH. Among the strains isolated, two showed characteristics of the Acetobacter genus (LBVE1 e LBVE4). Biomass production of the two strains were conduced on shaker flasks assays with three different ethanol concentrations as carbon source (10, 15 e 20 g/L) incubated in three different temperatures (30 35 e 37ºC). The highest biomass production for the two strains was obtained on the assays with 20 g/L ethanol, 30 ºC. However, both strains presented different growth conductions for the production of biomass highly active in NADindependent ADH. LBVE1 biomass produced on 10 g/L ethanol, 30ºC, showed the highest specific activity, 10.44 U/mg Proteín while the highest specific activity for LBVE4, 8.04 U/mg Proteín, was obtained on the biomass produced in assays with 15 g/L ethanol, 30 ºC. The results of the substrate specificity of the NAD-independent ADH present in the crude extract of both strains for selected primary and secondary alcohols. For primary alcohols, LBVE1 crude extract showed a decrease in the activity values with the rise of the carbon chain. Kinetic assays were performed to calculate apparent kinetics constants, using ethanol as substrate, for the NADindependent ADH present in the crude extract of both strains. LBVE1 crude extracts from cells grown in 10 and 20 g/L ethanol showed comparable values for Kmapp and VMax app. However, only extract from LBVE4 grown in 20 g/L ethanol had Kmapp value comparable to the one found for LBVE1 extracts analyzed.